2001
DOI: 10.1200/jco.2001.19.8.2206
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Patient Education and Coaching to Improve Pain Control Among Cancer Outpatients

Abstract: Compared with provision of standard educational materials and counseling, a brief individualized education and coaching intervention for outpatients with cancer-related pain was associated with improvement in average pain levels. Larger studies are needed to validate these effects and elucidate their mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
2
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(149 citation statements)
references
References 28 publications
2
136
2
9
Order By: Relevance
“…Data suggest that patients with advanced disease undergoing chemotherapy are able to successfully implement problem-solving strategies that reduce the severity of symptoms. The results of this study extend the work of other investigators who have reported on the effectiveness of CBIs in decreasing the severity of specific symptoms (Oliver et al, 2001) and for patients with a single cancer site (Antoni et al, 2001;Cruess et al, 2000). The results of this study extend support for using CBIs to affect multiple symptoms in patients with advanced disease across tumor types.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Data suggest that patients with advanced disease undergoing chemotherapy are able to successfully implement problem-solving strategies that reduce the severity of symptoms. The results of this study extend the work of other investigators who have reported on the effectiveness of CBIs in decreasing the severity of specific symptoms (Oliver et al, 2001) and for patients with a single cancer site (Antoni et al, 2001;Cruess et al, 2000). The results of this study extend support for using CBIs to affect multiple symptoms in patients with advanced disease across tumor types.…”
Section: Discussionsupporting
confidence: 79%
“…However, most studies have been limited to testing the effectiveness of CBIs in reducing the severity of a particular symptom, such as fatigue or pain (Oliver, Kravitz, Kaplan, & Meyers, 2001;Quesnel et al), or in patients who present with a particular site of cancer, such as breast cancer, regardless of the stage of disease Cruess et al, 2000). The goal of this study was to evaluate the effectiveness of a CBI in decreasing overall symptom severity in patients with advanced cancer undergoing chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…In a randomized trial, she compared this program to care-as-usual and found that the program significantly reduced pain intensity. Oliver and colleagues conducted a randomized trial with 78 patients with cancer (Oliver, Kravitz, Kaplan, & Meyers, 2001). Subjects in the intervention group received individualized information about misconceptions (based on scores on baseline measures of knowledge), supplemental information in a booklet, and coaching regarding communication with physicians about pain.…”
Section: Tests Of Educational Interventionsmentioning
confidence: 99%
“…Educating patients about their disease, its treatment, potential side effects, and qol can reduce anxiety 8 , enhance coping mechanisms 9 , reduce decisional conflicts, promote patient autonomy, and improve the patient experience 10 . Patients who understand their disease and its treatment also comply better with therapy 11 , which translates into better outcomes.…”
Section: Introductionmentioning
confidence: 99%